PENGELOLAAN KELAS DALAM MENINGKATKAN KEMAMPUAN BELAJAR SISWA - M. Badar (Al Hikmah: Jurnal Studi Keislaman, 2011)
Abstract: Classroom management can be divided into two kinds of physical management and student management. Harmonious relationships of student and teacher have an effect on classroom management. Teacher who are apathetic to student make the students away. Many students reject the presence of teachers. Envy is ingrained in students that cause unacceptable learning materials by students. The tendencies of students’ negative attitudes are more dominant. This hypocritical attitude created a gap between teachers and students. As with the teachers who always pay attention to students is always open, always responsive to student complaints, always listen to students' learning difficulties, always willing to listen to suggestions and criticism from students are the teachers who is liked by student. Students will miss his presence and advice was given. The classroom management strategies to improve students' learning ability is creating an atmosphere or condition of the optimal class, trying to stop the deviant behavior of students, creating a classroom discipline, creating harmony between teachers and students. Therefore, the task manager as a classroom teacher to always strive for dynamic conditioning class that supports the process of educational interaction achieving learning objectives.